Illegitimate Recombination Between Homeologous Genes in Wheat Genome - Liu, Chao; Wang, Jinpeng; Sun, Pengchuan; Yu, Jigao; Meng, Fanbo; Zhang, Zhikang; Guo, He; Wei, Chendan; Li, Xinyu; Shen, Shaoqi; Wang, Xiyin (Frontiers in Plant Science, 2020)
Polyploidies produce a large number of duplicated regions and genes in genomes, which have a long-term impact and stimulate genetic innovation. The high similarity between homeologous chromosomes, forming different subgenomes, or homologous regions after genome repatterning, may permit illegitimate DNA recombination. Here, based on gene colinearity, we aligned the (sub)genomes of common wheat (Triticum aestivum, AABBDD genotype) and its relatives, including Triticum urartu (AA), Aegilops tauschii (DD), and T. turgidum ssp. dicoccoides (AABB) to detect the homeologous (paralogous or orthologous) colinear genes within and between (sub)genomes. Besides, we inferred more ancient paralogous regions produced by a much ancient grass-common tetraploidization. By comparing the sequence similarity between paralogous and orthologous genes, we assumed abnormality in the topology of constructed gene trees, which could be explained by gene conversion as a result of illegitimate recombination. We found large numbers of inferred converted genes (>2,000 gene pairs) suggested long-lasting genome instability of the hexaploid plant, and preferential donor roles by DD genes. Though illegitimate recombination was much restricted, duplicated genes produced by an ancient whole-genome duplication, which occurred millions of years ago, also showed evidence of likely gene conversion. As to biological function, we found that ~40% catalytic genes in colinearity, including those involved in starch biosynthesis, were likely affected by gene conversion. The present study will contribute to understanding the functional and structural innovation of the common wheat genome.